Estudo de prevalência e incidência de reação sorológica positiva para toxocara em crianças matriculadas na primeira série do ensino fundamental público no município de Vitória-ES - Fragoso, Roberta Paranhos (2006)
Background. High prevalence of anti-Toxocara antibodies has been reported in inpatients at one reference pediatric hospital in Vitoria, but there was not any report of this prevalence in healthy children. Objectives. (a)To study the prevalence and incidence of Toxocara infection by searching anti Toxocara antibodies in schoolchildren seven to nine years old; (b) to investigate associated factors and to perform physical examination, including ophthalmologic examination, blood eosinophil counts and stool examinations for helminthes. Methods. A commercial ELISA IgG test for Toxocara was performed in 394 children (first series from elementary school).One year later the test was done again in all children with negative result in the first test (optical density under 0.250 ). Stool examination and blood counts were performed at a routine laboratory from the municipality of Vitoria. It was applied a questionnaire for information on hygiene and socioeconomic conditions. Ophthalmologic examination included eye grounds examinations. Results. Considering OD>>500 as a positive result, the serum prevalence was 51.6% (202/394) without gender differences. Eighteen, out of 92 children (19.5%) with negative result in the first test, presented a positive test one year later. At least one intestinal helminth was detected in 68/308 (22%) without gender differences. No significant differences were observed in the prevalence of positive serology in children with or without intestinal helminthes. Eosinophilia (blood ophils >400/mm3) was observed in 181/394 (45,9%) ,higher in children with positive serology, bearing or not intestinal helminthes Owning pets, low incomes, onycophagia and use of non filtered water were significantly associated with positive serology. No signs or symptoms related to Toxocara infection were observed in children with positive serology, except two cases of retinal lesions suggestive of ocular larva migrans. Conclusion. It was confirmed he high prevalence and it was demonstrated high incidence of positive serology in children in our county. Owning pets, low incomes, onycophagia and use of non filtered water were significantly associated factors. The absence of clinical manifestations and the low frequency of ocular lesions indicate that or Toxocara infection frequently is a benign, asymptomatic infection or the high prevalence observed was due to cross reaction with intestinal helminthes infections.